Geographic and seasonal variation of dissolved methane and aerobic methane oxidation in Alaskan lakes - Martinez-Cruz, K.; Sepulveda-Jauregui, A.; Walter Anthony, K.; Thalasso, F. (Biogeosciences, 2015)
Methanotrophic bacteria play an important role oxidizing a significant fraction of methane (CH4) produced in lakes. Aerobic CH4 oxidation depends mainly on lake CH4 and oxygen (O2) concentrations, in such a manner that higher MO rates are usually found at the oxic/anoxic interface, where both molecules are present. MO also depends on temperature, and via methanogenesis, on organic carbon input to lakes, including from thawing permafrost in thermokarst (thaw)-affected lakes. Given the large variability in these environmental factors, CH4 oxidation is expected to be subject to large seasonal and geographic variations, which have been scarcely reported in the literature. In the present study, we measured CH4 oxidation rates in 30 Alaskan lakes along a north-south latitudinal transect during winter and summer with a new field laser spectroscopy method. Additionally, we measured dissolved CH4 and O2 concentrations. We found that in the winter, aerobic CH4 oxidation was mainly controlled by the dissolved O2 concentration, while in the summer it was controlled primarily by the CH4 concentration, which was scarce compared to dissolved O2. The permafrost environment of the lakes was identified as another key factor. Thermokarst (thaw) lakes formed in yedoma-type permafrost had significantly higher CH4 oxidation rates compared to other thermokarst and non-thermokarst lakes formed in non-yedoma permafrost environments. As thermokarst lakes formed in yedoma-type permafrost have been identified to receive large quantities of terrestrial organic carbon from thaw and subsidence of the surrounding landscape into the lake, confirming the strong coupling between terrestrial and aquatic habitats and its influence on CH4 cycling.